2022
DOI: 10.1186/s12909-022-03427-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effectiveness of a course in major chemical incidents for front line health care providers: a pilot study from Saudi Arabia

Abstract: Background Mass chemical exposure emergencies are infrequent but can cause injury, illness, or loss of life for large numbers of victims. These emergencies can stretch and challenge the available resources of healthcare systems within the community. Political unrest in the Middle East, including chemical terrorist attacks against civilians in Syria and increasing chemical industry accidents, have highlighted the lack of hospital preparedness for chemical incidents in the region. This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Some content was about personal safety and security [ 49 , 50 , 55 , 204 – 206 , 208 , 209 ], waste management [ 66 , 212 , 299 ], mental health [ 95 , 105 , 166 , 172 , 177 , 213 , 221 , 235 , 259 , 277 , 293 ], infection control and prevention [ 139 , 168 , 241 , 264 , 302 ], pest control [ 65 , 66 , 70 , 212 , 216 , 299 ], triage [ 16 , 62 , 91 , 94 , 207 , 271 , 290 ] and stress management [ 31 , 182 , 270 ]. A smaller number of curricula included surgical training [ 98 , 99 , 165 , 323 ], time management [ 223 ], stigma [ 269 ], language and local culture [ 20 ], humanitarian law and leadership [ 102 ], chemical incidents [ 214 ] and dealing with ethical dilemma...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some content was about personal safety and security [ 49 , 50 , 55 , 204 – 206 , 208 , 209 ], waste management [ 66 , 212 , 299 ], mental health [ 95 , 105 , 166 , 172 , 177 , 213 , 221 , 235 , 259 , 277 , 293 ], infection control and prevention [ 139 , 168 , 241 , 264 , 302 ], pest control [ 65 , 66 , 70 , 212 , 216 , 299 ], triage [ 16 , 62 , 91 , 94 , 207 , 271 , 290 ] and stress management [ 31 , 182 , 270 ]. A smaller number of curricula included surgical training [ 98 , 99 , 165 , 323 ], time management [ 223 ], stigma [ 269 ], language and local culture [ 20 ], humanitarian law and leadership [ 102 ], chemical incidents [ 214 ] and dealing with ethical dilemma...…”
Section: Resultsmentioning
confidence: 99%
“…On training methods, 68 studies [ 13 17 , 20 25 , 27 30 , 32 , 33 , 37 , 41 , 45 , 47 , 48 , 53 , 58 , 59 , 62 , 65 , 68 , 79 , 84 , 85 , 87 , 88 , 90 , 93 , 97 , 111 , 123 125 , 138 , 141 , 145 , 146 , 148 , 153 , 161 , 167 , 168 , 170 , 193 , 204 , 214 , 216 , 247 , 251 , 255 , 261 , 294 , 297 , 298 , 300 , 304 , 313 , 321 , 322 …”
Section: Prominent Topic Areasunclassified
“…Blended learning is a combination of remote and face-to-face and synchronous and asynchronous teaching methods ( 35 ). Prior studies have demonstrated that blended learning is one of the most effective teaching methods in disaster medicine, via multiple teaching strategies it provides the opportunity to teach broad aspects of knowledge and skills ( 36 ). In addition, simulation-based training, such as tabletop exercises, drill, functional and full-scale exercise, and virtual reality simulation exercises, has become a realistic and effective approach to prepare the first responders for disaster management and increase the learner knowledge, enhance self-confidence and refine the skills ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 Three papers were excluded as they were set in Saudi Arabia, which was assessed as too dissimilar to the Australian population and health-care system. [29][30][31] A further 3 studies were excluded as English translations were not available. [32][33][34] Thus, after full text screening, 11 relevant articles were retained.…”
Section: Search Strategymentioning
confidence: 99%